Echolocating bats rely on an innate speed-of-sound reference - Amichai, Eran; Yovel, Yossi (Proceedings of the National Academy of Sciences - PNAS, 2021)
Animals must encode fundamental physical relationships in their brains. A heron plunging its head underwater to skewer a fish must correct for light refraction, an archerfish shooting down an insect must “consider” gravity, and an echolocating bat that is attacking prey must account for the speed of sound in order to assess its distance. Do animals learn these relations or are they encoded innately and can they adjust them as adults are all open questions. We addressed this question by shifting the speed of sound and assessing the sensory behavior of a bat species that naturally experiences different speeds of sound. We found that both newborn pups and adults are unable to adjust to this shift, suggesting that the speed of sound is innately encoded in the bat brain. Moreover, our results suggest that bats encode the world in terms of time and do not translate time into distance. Our results shed light on the evolution of innate and flexible sensory perception.